Efforts To Improve Physical Fitness Through Slagball Games in Students of SD Negeri Petanggan Belitang Mulya, East Oku Regency - Arizal, Nursidiq; Kristina, Putri Cicilia; Hermansah, Bambang (Yayasan Sembilan Pemuda Indonesia, 2023)
The purpose of this study was to determine the Physical Fitness Level of elementary school students through the Burnball/Slag ball Game. The population in this study were 40 students in grade V of SD Negeri Petanggan for the 2021/2023 school year. The sampling technique used is total sampling. For data analysis use the Action Research method with a percentage descriptive analysis pattern or percentage correction. To find out the initial condition of the sample, we held a preliminary test with the Bleef test instrument, which is to determine the level of freshness of the female students. From the results of the sample, students were then given slag ball game practice for 3 weeks in the first cycle and 3 weeks in the second cycle. After receiving treatment for 6 weeks, a test is held at the end of each cycle with the same test instrument. These results then processed with the analysis used is by percentage descriptive analysis or percentage correction. Based on data analysis on the initial test, it was obtained that it can be said that caste games can improve the physical fitness of elementary school age. From the results of this study, it is recommended that physical education teachers of SD Negeri Petanggan Oku Timur can use slag ball games to improve the physical freshness of their students.